The Reception and Dissemination of the Analects in Ancient Japan - Jing ZHAO (Forest Chemicals Review)
The Analects has been highly valued and influenced all aspects of Japanese politics, ideology and culture since it was introduced to Japan. The dissemination of the Analects varied rather widely under different historical contexts. This study aims to investigate the reception of the Analects and its commentaries at different development stages in ancient Japan, and to analyze the changes of the way Analects was studied, the reception purposes and the dissemination class in different periods of ancient Japan, thereby outlining the development contrail of the Analects in Japan and providing a glimpse of its role in cultural exchange between China and Japan.